365 Days of Belonging, Activism and Change: Examining the perception of minorities in the UK in the wake of the Black Lives Matter Summer - ETHAN MILLS (2022)
This research examines the perception of racial and ethnic minorities within the UK, in response to the Black Lives Matter protests that occurred over the summer of 2020, focusing upon the south Wales region. Explored through themes of the everyday, activism and change, the research addresses the historic place of minorities within society. These ideas are then developed in connection with a number of case studies that detail examples of how the perception of minorities has changed over time, and as a direct result of the Black Lives Matter movement. Alongside this, qualitative data collected from interviews with minorities of varying ages and backgrounds allows for a focus on their own thoughts and feelings, thus creating a new dialogue that juxtaposes a more traditional, academic view on issues of race, racism and social justice. It is through these discussions that many of the key themes of the research are addressed and subsequently developed in order to gain a better understanding of how racial and ethnic minorities’ lived experiences and place within modern society impacts the wider perception and education around issues of race and racism. This research project aims to develop tools and educational avenues through which a better understanding of race and racism, and those affected by it, can be developed, in the hope of advancing attitudes and understandings of anti-racism and its newfound significance in an ever increasing multi-racial and multi-ethnic world.